Factors Affecting Patient’s Satisfaction In Outpatient Clinics - Alghamdi, Salah Hassan; Alhazmi, Ghaida Ali; Alotaibi, Sultan Dawei; Almalki, Khalid Awad Saleh; Alzahrani, Khalid Othman Haris; AL sahli, Mohammed Nasser Abdullah; Aldosari, Ibraheem Fardous; Zinab Darwish Almuwallad; Abdulrahman Ahmed Mohammed Alzahrani; Mjed Omar Abdullah Balubaid; Faiz Abdullah Ahmed AlNebate (Migration Letters, 2023)
Background: Every healthcare institution aims to reach the highest quality of care. Quality of care comprises the structure, the process, and the outcome of the care. In this study, we will assess the structure and the process of healthcare system that can affect patient’s general satisfaction. Methods: In this cross-sectional study, we surveyed patients visiting outpatient’s clinics at Makkah hospitals. We focused on aspects that are, according to previous studies, significantly affecting patient’s satisfaction; these include interaction with all healthcare providing personnel, time needed to complete different services, general cleanliness, and food services. Re[1]sults: A total of 215 participants were included in this study, there were 77 (36%) men and 138 (64%) women. the mean score differences between those who rated their impression as “poor” and those who rated it as “excellent” were as following: interaction score, mean difference of 13.3 [95% confidence interval (CI): 6.4 to 20.19; P<0.001]; timing score, mean difference of 2.61 (95% CI: 0.12 to 5.35; P=0.044); cleanliness score, mean difference of 6.44 (95% CI: 3.81 to 9.08; P<0.001); and food score, mean difference of 5.07 (95% CI: 2.37 to 7.76; P<0.001). Conclusions: Focusing on all aspects affecting patient’s satisfaction can both improve the general impression about the facility and increase patient’s loyalty to it.